2003
DOI: 10.1046/j.1461-0248.2003.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer‐resource stoichiometry in detritus‐based streams

Abstract: Stoichiometric relationships between consumers and resources in detritus‐based ecosystems have received little attention, despite the importance of detritus in most food webs. We analysed carbon (C), nitrogen (N), and phosphorus (P) content of invertebrate consumers, and basal food resources in two forested headwater streams (one reference and the other nutrient‐enriched). We found large elemental imbalances between consumers and food resources compared with living plant‐based systems, particularly in regard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
422
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(476 citation statements)
references
References 43 publications
44
422
10
Order By: Relevance
“…Phototrophs, unlike herbivores, can adjust their elemental composition depending on nutrient stoichiometry, resulting in different food quality and thus affecting consumption rates and consumer nutrient recycling [8]. In community ecology, ES has successfully been used to explain consumer performance (food uptake rate, assimilation, growth rate and efficiency; [9][10][11]), competition between consumer species [12,13], and consumer effects on prey nutrient composition [14,15]. In contrast to ES, MTE [16] focuses on consumer body mass and temperature as determinants of metabolic rates, which control growth and consumption rates as well as population and community productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Phototrophs, unlike herbivores, can adjust their elemental composition depending on nutrient stoichiometry, resulting in different food quality and thus affecting consumption rates and consumer nutrient recycling [8]. In community ecology, ES has successfully been used to explain consumer performance (food uptake rate, assimilation, growth rate and efficiency; [9][10][11]), competition between consumer species [12,13], and consumer effects on prey nutrient composition [14,15]. In contrast to ES, MTE [16] focuses on consumer body mass and temperature as determinants of metabolic rates, which control growth and consumption rates as well as population and community productivity.…”
Section: Introductionmentioning
confidence: 99%
“…A Kruskal-Wallis ANOVA was used to test for significant differences in elemental ratios of larvae between different treatments. In addition, we plotted the elemental ratios of larvae and food resources (C:N, C:P and N:P) to check the relative stoichiometric constraints (i.e., elemental imbalances) naturally existing in these ecosystems and go through potential changes due to alterations of environmental and dietary conditions (Sterner and Elser, 2002;Cross et al, 2003).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Recent studies have shown that the degree to which shredders modify FPOM stoichiometry from CPOM stoichiometry may also vary across shredder species depending on traits such as nutritional requirements or feeding behaviour when reared under different leaf types and temperatures (Villanueva et al, 2011;Mas-Martı´et al, 2015;Correa-Araneda et al, 2015). The order Diptera is known to have a high P content, although paradoxically, detritus is among the most P-deficient of food resources (Cross et al, 2003;Evans-White et al, 2005). In our detritus-based system, we confirmed that B. bifida larvae are clearly far out of stoichiometric balance with their food resources, mostly in eucalypt treatments (where the highest elemental imbalances occurred).…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations